2013
DOI: 10.1099/vir.0.046896-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of bluetongue virus serotype 4 field isolates from Argentina

Abstract: Bluetongue is an insect-transmitted viral disease of ruminant species, which represents a major barrier to the international trade of animals and their products. Bluetongue virus (BTV) has a genome composed of ten linear segments of dsRNA, which code for at least ten different viral proteins. In South America, serological evidence for the presence of BTV has been found in Peru, Argentina, Brazil, Ecuador and Chile. Brazil and Argentina are the only South American countries where BTV has been isolated. In Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
2
29
0
1
Order By: Relevance
“…BTV-10, 12, 14, 13, 17 and 24 had been previously identified in South America (Homan et al, 1985;Lancelot et al, 1989). More recently BTV-4 was isolated in Argentina and Brazil (Legisa et al, 2013(Legisa et al, , 2014.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…BTV-10, 12, 14, 13, 17 and 24 had been previously identified in South America (Homan et al, 1985;Lancelot et al, 1989). More recently BTV-4 was isolated in Argentina and Brazil (Legisa et al, 2013(Legisa et al, , 2014.…”
Section: Discussionmentioning
confidence: 98%
“…In the 1980s, a major program of sentinel herds has shown that 3,4,6,8,12,17 were circulating in Central America and the Caribbean region, presumably without clinical expression (Mo et al, 1994). In South America, the only serotypes detected by virological methods (virus isolation or genome detection by Polymerase Chain Reaction) were serotype 4 in Brazil in 1979 and more recently in Argentina (Lager et al, 2004;Legisa et al, 2013) and serotype 12 in the southern provinces of Brazil in two clinical episodes in 2001 (Clavijo et al, 2002).…”
mentioning
confidence: 97%
“…3 A phylogenetic analysis revealed a South American genetic identity for the Argentine sequences, indicating the independent evolution of this viral lineage. 5 There are still no contingency plans for responding to an outbreak of bluetongue disease in Brazil. Therefore, when vesicular disease is suspected, the Animal Defense Office initiates procedures developed against foot-and-mouth disease.…”
mentioning
confidence: 99%
“…In previous works, our group characterized Argentine isolates as a well-differentiated independent lineage [25]. However, the similarity analysis performed (data not shown) including amino acid sequences and comparing welldefined groups showed that the Argentine group and worldwide BTV4 isolates were highly similar and conserved the regions previously recorded as antigenic sites [31,32].…”
Section: Discussionmentioning
confidence: 90%
“…BTV serotype 4 (BTV4) strain used in this study was an Argentine isolated named 4/ARG/829/2001, described by Legisa [25,26]. Segment 2 (Seg2) open reading frame was cloned into pFastBacDual plasmid (Invitrogen).…”
Section: Construction Of Recombinant Baculovirusesmentioning
confidence: 99%